A new approach for improving access to primary care and public health in India: the 3T Model. - Saha, Satadal; Basu, Bibaswan; Mukherjee, Ruchira (Health Promotion Perspectives, 2025)
Health inequities in India encompass limited primary care access, dearth in healthcare personnel, especially in rural fragile geographies. A health system strengthening (HSS) approach through an innovative 3T-model can solve this ubiquitous problem. 3T includes- (i) Train rural youths (majorly women) as nationally certified & digitally literate Community Health Workers (CHWs) creating livelihood and women empowerment (ii) Technology: clinical algorithm driven software; easy-to-use affordable innovative diagnostic devices, screening tools (iii) Task-shifting: the software guides CHWs transmit structured, analysable, patient data to 'remote' doctors. CHWs addresses personnel shortage in health sector. Technology and task-shifting enable improved access to general and specialist doctors. Digital presence reduces doctors' travel and time, enabling more consultations. The 3T-model addresses critical health inequities in India. Effective scaling can significantly improve access to affordable primary care and public health services for last-mile populations with potential to reduce gender disparities in access to essential healthcare.